Keputusan Pemberian Kredit Kepada UMKM Dalam Peer-To-Peer Lending: Faktor-Faktor Apa Saja Yang Dipertimbangkan Investor? - Dyta Listalia; Diah Hari Suryaningrum (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine and demonstrate six factors influencing the decision to grant credit loans to MSMEs on the conventional Peer-to-peer (P2P) lending platforms Investree and Koinworks. These six factors are loan amount, loan term, credit rating, loan purpose, business duration, and financial statement information. A quantitative approach and secondary data from the publications of the Investree and Koinworks applications or websites were utilized in this research. A sample of 225 MSMEs was selected from a population of 267 using purposive sampling. Logistic regression analysis revealed that loan amount, credit rating, and loan purpose affect MSMEs on the Investree and Koinworks P2P lending platforms, while loan term, business duration, and financial statement information do not. These findings suggest that both P2P lending platforms consider various factors when evaluating MSME borrowers. The differences between Investree and Koinworks indicate distinct characteristics and appeals to MSMEs on each platform, which are also discussed in this study. The results of this research can assist MSMEs in preparing loan proposals to enhance credibility with lenders, provide better insights to lenders in decision-making, and serve as a reference for other P2P lending platforms in evaluating factors necessary for credit loan decision-making processes.